SDF-1 induces TNF-mediated apoptosis in cardiac myocytes - Jarrah, Andrew A. (Apoptosis, 2018)
Chemokines are small secreted proteins with chemoattractant properties that play a key role in inflammation. One such chemokine, Stromal cell-derived factor-1 (SDF-1) also known as CXCL12, and its receptor, CXCR4, are expressed and functional in cardiac myocytes. SDF-1 both stimulates and enhances the cellular signal which attracts potentially beneficial stem cells for tissue repair within the ischemic heart. Paradoxically however, this chemokine is known to act in concert with the inflammatory cytokines of the innate immune response which contributes to cellular injury through the recruitment of inflammatory cells during ischemia. In the present study, we have demonstrated that SDF-1 has dose dependent effects on freshly isolated cardiomyocytes. Using Tunnel and caspase 3-activation assays, we have demonstrated that the treatment of isolated adult rat cardiac myocyte with SDF-1 at higher concentrations (pathological concentrations) induced apoptosis. Furthermore, ELISA data demonstrated that the treatment of isolated adult rat cardiac myocyte with SDF-1 at higher concentrations upregulated TNF-α protein expression which directly correlated with subsequent apoptosis. There was a significant reduction in SDF-1 mediated apoptosis when TNF-α expression was neutralized which suggests that SDF-1 mediated apoptosis is TNF-α-dependent. The fact that certain stimuli are capable of driving cardiomyocytes into apoptosis indicates that these cells are susceptible to clinically relevant apoptotic triggers. Our findings suggest that the elevated SDF-1 levels seen in a variety of clinical conditions, including ischemic myocardial infarction, may either directly or indirectly contribute to cardiac cell death via a TNF-α mediated pathway. This highlights the importance of this receptor/ligand in regulating the cardiomyocyte response to stress conditions.